Feasibility Test of Hanging Sacks with Coconut Coir Waste Filling Materials for Martial Arts - Firdaus, Rizki; Mardela, Romi; Argantos, Argantos; Setiawan, Yogi (International Martial Arts and Culture Journal, 2024)
Studi Purpose The problem in this study is the lack of interest among martial arts activists in utilizing sports equipment products that have not been proven to be of proven quality. Many factors cause it. For this reason, the researcher will only discuss the feasibility test of making hanging bags using coconut coir waste for martial arts. Method This type of research is qualitative, this research was carried out in January 2023. The population in the study is all athletes of the Indonesian Pariaman Satria Young Pencak Silat College which totals 32 athletes. Samples were taken only from 30 athletes by purposive sampling. Data collection using tests, with the following instruments: Using a Questionnaire. Test from martial artists and coconut fiber waste material processing experts. Result and Discussion The The results of the research are data analysis that illustrates the feasibility of Samsat Hanging With Coconut Coir Valley Stuffing Material for Pencak Silat Martial Arts Satria Muda Indonesia 1) Small Group Test has 5 people with a percentage of 17% of athletes interested in the very strong category, 25 athletes are categorized as Strong with a percentage of 83%.  The percentage of Hanging Bag Eligibility from the results of martial artists 64% in the good category and the results of waste experts 86% are very good. 2) Martial artist test Based on the analysis of the martial artist test, the score obtained was 34, the maximum score was 50, the percentage was 64% Categorized Good. 3) Based on the analysis of the material processing expert test, the score was obtained 43, the maximum score was 50, the percentage of 86% was categorized as Very Good. Feasibility This tool is filled with coconut fiber valley filled with coconut fiber, and is even ready to be used without revision, this tool is also suitable for use in martial arts, and is even ready to be tested without revision.